Effect of anulom vilom pranayama as an adjuvant treatment modality to improve the level of dyspnea in chronic asthma patients - Jose, Jane Mary; Thomas, Vadakken Devassy; Janso, Kollanur (International Journal of Advances in Medicine, 2018)
Background: Dyspnea is the main symptom suffered by bronchial asthma patients who are even under medical treatment. This study was aimed to evaluate the use of alternate nostril breathing as an adjuvant treatment modality to improve the level of dyspnea in patients with bronchial asthma. Methods: Patients who were diagnosed to have bronchial asthma for more than 6 months with the modified Borg dyspnea score of more than 3 and forced expiratory volume (FEV1) for one second less than 80% included in the study. Anulom Vilom Pranayama was instructed to practice daily for 10 minutes for 4 weeks. The level of dyspnea in pre and post test was conducted using modified Borg dyspnea scale after doing six minute walk. Spirometer was used to assess the FEV1. The data was analysed statistically. Results: Twenty patients were included in the study. Majority belonged to the age group of 20-29 with female dominance and no history of smoking. There was a significant (p = 0.0001) reduction in dyspnea after practicing Anulom Vilom Pranayama for one month. The median of Borg dyspnea scale in the pre-test was 4.5 and that of post-test was 3.5. The mean FEV1 score in the pre-test was 57.20 and that of post-test was 68.75 which was found to be statistically significant (p=0.0001). Conclusions: One-month anulom vilom pranayama daily for 10 minutes improved the Borg dyspnea scale and FEV1 score. This indicates it as an effective intervention in reducing the level of dyspnea in chronic bronchial asthma patients.